A case report of isolated orbital vasculitis mimicking retinal migraine: A potential cause of recurrent transient monocular blindness and ipsilateral headache. (May 2019) - Park, Ji-Hyung; Park, Kyung-Ah; Cha, Jihoon; Kim, Sung Tae; Chung, Chin-Sang; Lee, Mi Ji
Background: Retinal migraine is an important differential diagnosis of recurrent transient monocular blindness accompanied by headache when other etiologies are excluded. Here, we report a case of orbital vasculitis which initially mimicked retinal migraine. Case report: A 47-year-old woman had recurrent episodes of fully reversible transient monocular blindness accompanied by ipsilateral headache for 15 months. The patient's neuroimaging and cardiac and ophthalmologic evaluations were normal. With a diagnosis of retinal migraine, her symptoms remitted in response to prophylactic treatment with topiramate and propranolol for 8 months. Three months after discontinuation of medications, transient monocular blindness recurred. High-resolution vessel wall magnetic resonance imaging revealed enhancement of the ipsilateral orbital vessels. Isolated orbital vasculitis was diagnosed. Complete remission of transient monocular blindness was achieved after steroid pulse therapy. Discussion: Isolated orbital vasculitis should be considered in differential diagnosis of recurrent transient monocular blindness and ipsilateral headache. High-resolution vessel wall magnetic resonance imaging can be helpful for the diagnosis.